Identity, intertextuality, and performance in early modern song culture - Poel, Dieuwke van der; Grijp, Louis Peter; Anrooij, Wim van (Intersections, 2016)
Local and religious identity in Swedish popular hymn singing during the seventeenth and eighteenth centuries / Ingrid Akesson -- Performing pietism in the peatlands : songs in the manuscript miscellany of a village schoolmaster in the Dutch republic between 1750 and 1800 / Nelleke Moser -- Guilielmus Bolognino's Den gheestelijcken leeuwercker : the collected songs of a counter-reformation champion / Hubert Meeus and Tine de Koninck -- Songs and identities : handwritten secular songbooks in German-speaking areas of the fifteenth and sixteenth centuries / Franz-Josef Holznagel -- 'Social networking is in our DNA' : women's alba amicorum as places to build and affirm group identities / Sophie Reinders -- The many shades of love : possessors and inscribers of sixteenth-century women's alba / Clara Strijbosch -- Exploring love's options : song and youth culture in the sixteenth century Netherlands / Dieuwke van der Poel -- Oppositional political identity in the song culture of the Vormarz and the 1848 revolution in Germany / David Robb -- The perils of performance : from political songs to national airs in romantic-era Wales (1790-1820) / Mary-Ann Constantine -- Folksongs, conflicts and social protest in early modern France / Eva Guillorel -- "Fortune my foe" : the circulation of an English super-tune / Christopher Marsh -- Samuel Pepys and the making of ballad publics / Patricia Fumerton -- Slave orchestras and rainbow balls : colonial culture and creolisation at the Cape of Good Hope, 1750-1838 / Anne Marieke van der Wal.